Exploring New Arabic Semantic Paradigms For Understanding The Quran Addressing Interpretive Gaps and Hidden Meanings - Ismail, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research proposes a new semantic approach to enhance the understanding of Arabic text in the Quran context. The aim is to bridge the existing gap in interpretation, which primarily relies on semantic web ontology and the linguistic framework developed by Toshihiko Izutsu. This philosophical research seeks to provide new paradigms and transcend the conventional semantic. It argues for the adoption of five methodical steps to uncover the deeper meanings behind the literal text of the Quran: (a) textual context analysis, (b) situational context analysis, (c) integration of intrinsic and extrinsic elements of the Quran, (d) syntagmatic and paradigmatic analysis, and (e) constructing the meaning of the past and present. This new paradigm challenges the traditional semantic approach to the Quran and facilitates a deeper understanding.